Komunikasi Politik Tokoh Agama Pada Pilkada Serentak Tahun 2020 (Study Ustadz Abdul Somad) - Ivan Sunata; Ahmad Khairul Nuzuli; Muhammad Munir (Institut Agama Islam Negeri (IAIN) Curup, 2022)
This research broadly aims to reveal the role of ulama as political communicators and specifically to reveal the involvement of Ustadz Abdul Somad (UAS) in the perspective of political communication in the 2020 Pilkada. The results show that of the three kinds of political communicators, Ustadz Abdul Somad (UAS) falls into the third, namely the spokesperson and opinion leader. Because the goal is not to gain a position, but to provide support because of the same vision, mission and goals. UAS is also a highly charismatic person in the community, so it is believed to be able to move people to make political choices in the political contestation in the 2020 Pilkada. The political messages conveyed by UAS in the 2020 Pilkada are as follows: a) Politics is part of community education, b) Politics is a means to apply da'wah, c) Resist political pressure, d) Reject money politics.